Research on the contact characteristics and modification of axle sleeve type spline pair of gauge-changeable wheelset - TANG Jiacheng; HUANG Zhihui; PENG Yueyang; JIANG Xutao (机车电传动)
Regarding the contact problem of axle sleeve type spline pair in the wheel axle structure of 1 435 mm/1 520 mm gauge-changeable bogie with a speed of 400 kilometers per hour, the contact pressure distribution was studied under different gauge and misalignment angles, and the influence of crowned modification and gear tip rounding on the contact pressure distribution on the tooth surface of spline pair was studied in the paper with ABAQUS software. The calculation results show that: the maximum contact pressure on the tooth surface of the spline pair increases with the increase of misalignment angle, and the contact pressure on the broad gauge is greater than that on the standard gauge; when there is angular misalignment, crowned modification significantly reduces the maximum contact pressure of the spline, as the amount of modification quantity increases, the compensation ability of the spline for angular misalignment becomes stronger; the crowned shaped axle sleeve type spline pair has an misalignment angle range, which causes the maximum contact pressure of the spline pair to be smaller on the broad gauge than on the standard gauge, and the angle range increases as the amount of modification quantity increases; the edge effects in the direction of tooth profile is improved after the crowned shaped axle sleeve type spline pair is rounded at the gear top, further reducing the maximum contact pressure.